Study of carbon black-epoxy based fat tissue phantom and its dielectric properties / Hatem Mohamed Abdelwahab Al-Gabroun - Hatem Mohamed, Abdelwahab Al-Gabroun (2010)

(untitled)
Microwave imaging techniques for medical applications have been reported in the literature for many years. However, the progress in imaging algorithms, numerical techniques, microwave hardware and computational speed has renewed the interest in this field. Breast cancer detection is particularly attractive from a microwave imaging perspective, the major reason referred to the potentially high dielectric contrast between cancerous tissues and normal breast tissues depending on water content. Low water tissues tend to be low permittivity as fat, whilst high water content tissues tend to be high permittivity as cancerous tissues. All of that increased the need for effective phantoms that mimic the electromagnetic properties of biological tissues at these high frequencies in a purpose of testing the mutual effects between these radiations and biological tissues. For this purpose several phantoms with several materials have been proposed to simulate bio logical tissues. This study investigates a simulation method based on rule of mixture to design fat phantom by using binary system containing epoxy as a matrix and carbon black powder as a filler. The dielectric properties were measured by using Network Analyzer equipped with coaxial cable and the results showed the possibility of using this system for fat tissues simulating at frequency range from I G Hz to I 0 G Hz.